Randomized, controlled trial of miglustat in Gaucher’s disease type 3 - Schiffmann, Raphael; Ries, Markus (Annals of neurology, 2008)
Objective - To evaluate the efficacy and safety of miglustat, concomitant with enzyme replacement therapy (ERT), in patients with Gaucher’s disease type 3 (GD3). - - Methods - This 24-month, phase II, open-label clinical trial of miglustat in GD3 was conducted in two phases. During the initial 12 months, patients were randomized 2:1 to receive miglustat or “no miglustat treatment.” The randomized phase was followed by an optional 12-month extension phase in which all patients received miglustat. All patients received ERT during the 24-month period. The primary efficacy end points were change from baseline to months 12 and 24 in vertical saccadic eye movement velocity as determined by the peak amplitude versus amplitude regression line slope. Secondary end points included changes in neurological and neuropsychological assessments, pulmonary function tests, liver and spleen organ volumes, hematological and clinical laboratory assessments, and safety evaluations. - - Results - Thirty patients were enrolled, of whom 21 were randomized to miglustat and 9 to “no miglustat treatment.” Twenty-eight patients entered the 12-month extension phase. No significant between-group differences in vertical saccadic eye movement velocity or in the other neurological or neuropsychological evaluations were observed. Organ volumes and hematological parameters remained stable in both treatment groups, but improvement in pulmonary function and decrease of chitotriosidase levels were observed with miglustat compared with patients receiving ERT alone. - - Interpretation - Miglustat does not appear to have significant benefits on the neurological manifestations of GD3. However, miglustat may have positive effects on systemic disease (pulmonary function and chitotriosidase activity) in addition to ERT in patients with GD3.
Gesehen am 09.05.2019